Correlation between Age and Body Mass Index (BMI) with Histopathological Features of Breast Cancer Patients in RSUP Haji Adam Malik Medan - Harisa Mardiah; Radita Nur Anggaeni Ginting; Heru Rahmadhany; Esther Reny Deswani Sitorus (Indonesian Journal of Cancer, 2021)
Background: Breast cancer is influenced by various risk factors, including age and obesity. Older women who are overweighted and obese have a higher risk of developing breast cancer. This study aims to find the correlation between age and body mass index (BMI) with histopathological features of breast cancer patients in RSUP Haji Adam Malik Medan.Methods: This research is an analytical study using a cross-sectional design with 103 samples obtained from medical record data by random sampling. The data obtained were then adjusted to the research criteria and grouped based on predetermined variables.Results: The majority of the age group was 41-50 years (36.9%), obesity BMI (40.8%), histopathological subtype of invasive carcinoma of no special type (NST) (85.4%), and grade II (46.6%). Kruskal-Wallis test result between histopathological subtypes and breast cancer grading based on age, respectively, obtained p=0.503, r=.325; (α>0.05), and p=0.207, r=0.393; (α>0.05), while based on BMI obtained p=0.017, r=0.021; (α<0.05), and p=0.018, r=0.018; (α<0.05). The OR value (95% CI) obtained on overweight-obese BMI with invasive carcinoma NST subtype was 7.63 (7.27–14.90) and other subtypes were 2.40 (1.14–13.75), and for grades II and III, they were respectively 3.57 (1.32–8.09) and 3.27 (1.17–9.91).Conclusions:  There was a correlation between BMI with histopathological subtypes and breast cancer grading, but the correlation tended to be weak. Whereas, with age, there was no correlation. BMI overweight-obese were more likely to have invasive carcinoma NST subtype and higher-grade of breast cancer.